MO489GESTATIONAL DIABETES AND THE LONG-TERM RISK OF MATERNAL KIDNEY DISEASE: A SWEDISH NATIONAL COHORT STUDY. (29th May 2021) - Barrett, Peter; McCarthy, Fergus; Evans, Marie; Kublickas, Marius; Perry, Ivan; Stenvinkel, Peter; Kublickiene, Karolina; Khashan, Ali
Abstract: Background and Aims: Gestational diabetes (GDM) is increasingly common worldwide. GDM is associated with increased risk of type 2 diabetes (T2DM) and cardiovascular disease in women. It is uncertain whether GDM is independently associated with long-term risk of maternal kidney disease. We aimed to examine the association between GDM and maternal chronic kidney disease (CKD) and end-stage kidney disease (ESKD) and to determine whether this depends on progression to overt T2DM. Method: A nationwide retrospective cohort study was designed using data from the Swedish national registers. Women were included if their first delivery occurred between 1 January 1987 and 31 December 2012. Previous GDM was the main exposure variable, and this was stratified according to whether women developed T2DM after pregnancy. We estimated the risk of CKD, ESKD and different CKD subtypes (tubulointerstitial, glomerular, hypertensive, diabetic, other/non-specific). Cox-proportional hazard regression models were used with time-dependent covariates. We adjusted for a wide range of confounders including maternal age, country of origin, maternal education, parity, antenatal BMI, gestational weight gain, smoking during pregnancy and preeclampsia. Results: There were 1, 121, 633 women included, of whom 15, 595 (1.4%) had a diagnosis of GDM. Overall, GDM-diagnosed women were at increased risk of CKD (aHR 1.81, 95% CI 1.54-2.14) and ESKD (aHR 4.52, 95% CI 2.75-7.44). Associations were strongest for diabetic CKD (aHR 8.81, 95% CI 6.36-12.19), hypertensive CKD (aHR 2.46, 95% CI 1.06-5.69), and glomerular CKD (aHR 1.86, 95% CI 1.37-2.51). However, these associations were largely explained by progression to post-pregnancy T2DM. Among women who had GDM + subsequent T2DM, strong associations were observed with CKD (aHR 21.70, 95% CI 17.17-27.42) and ESKD (aHR 112.37, 95% CI 61.22-206.38). By contrast, women who only experienced GDM (and no future T2DM) were not at significantly higher risk of CKD (aHR 1.11, 95% CI 0.89-1.38) or ESKD (aHR 1.58, 95% CI 0.70-3.60). Conclusion: Women who experience GDM are at increased risk of CKD and ESKD if they develop T2DM. However, GDM-diagnosed women who do not develop overt T2DM in later life have a similar risk of CKD/ESKD to those with uncomplicated pregnancies.